No DDRama at chromosome ends: TRF2 takes centre stage. Issue 5 (May 2015) - Feuerhahn, Sascha; Chen, Liuh-yow; Luke, Brian; Porro, Antonio
Highlights Distinct molecular properties of TRF2 dictate different states of telomere protection. TRF2 promotes assembly of higher-order structures at telomeres. TRF2 remodels the telomeric chromatin environment. TRF2 regulates TERRA transcription.